The Effect of Addition Purple Sweet Potato Extract (Ipomea batatas L.) and Storage at 4oC on the Antioxidant and Antibacterial Activities of Yogurt - Pare, Regina Londong; Budiarso, Tri Yahya; Amarantini, Charis (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Yogurt is one of the fermented dairy products produced by lactic acid bacteria from milk, which contains beneficial nutritional components for human health. The innovation of yogurt production with the addition of probiotic cultures and food ingredients containing bioactive compounds can enhance its quality. This research aims to investigate the effect of adding purple sweet potato extract and storage treatment at 4℃ on yogurt's antioxidant and antibacterial activities. Four treatments were conducted in yogurt production, namely without adding purple sweet potato extract and adding 5%, 10%, and 15% (v/v) extract. All treatments were fermented using Lactobacillus bulgaricus, Streptococcus thermophilus, and Lactobacillus plantarum S1K2T1 as starter cultures. Subsequently, the yogurt was stored at 4℃ for 6 days, and chemical parameters, antioxidant, and antibacterial activities were examined. The highest result was observed in the treatment with 15% addition, showing a total antioxidant activity of 70.98% and an IC50 value of 13.96 ppm, which is equivalent to 2.06 times that of 200 ppm ascorbic acid. The six days storage affected antioxidant activity, but it was not significantly different. The antibacterial test showed indications of inhibition against Staphylococcus aureus ATCC 25923, Salmonella typhi NCTC 786, and Escherichia coli ATCC 25922, although the effect was very weak.